O preconceito racial em crianças na cidade de Alagoinhas, Bahia - Santos, Rozelia dos Anjos Oliveira (2017)
This dissertation presents a study which aimed at analysing racial prejudice in white and non-white children in the city of Alagoinhas-Bahia. It is particularly verified the stereotypes attributed to black and white people groups and racial discrimination. In order to achieve those objectives, the main concepts and researches on the theme were analysed as well as an empirical study presented in three chapters, besides the introduction and final considerations. In the introduction, general aspects on prejudice in society are presented as well as the organization of the text. In Chapter I, the racial prejudice and its main aspects are debated. In Chapter II, the socialisation of prejudice and prejudice during childhood are discussed. In Chapter III, the methodological aspects of the empirical study are presented, and this study had a sample of 112 children aged 5 to 12 years. In Chapter IV, the main results and discussion were presented. The results of the empirical study related to the stereotypes evidenced that regardless the skin colour, the participants attributed more negative traits to black people than white ones. Moreover, younger children attributed more negative traits than older children. Concerning preferences, the participants preferred white children, and younger children choose the white ones to be their sibling, friend or to give the sweet. Overall, it was observed that the participants discriminate the black target and younger children discriminate more in comparison to older ones. These results were discussed based on the theories of socialisation of prejudice. Finally, in the final considerations, the implications of these results are discussed in relation to studies on prejudice during childhood and some thoughts on future studies.